Vibration-Driven Microrobot Positioning Methodologies for Nonholonomic Constraint Compensation - Kostas Vlachos; Dimitris Papadimitriou; Evangelos Papadopoulos (Engineering, 2015)
This paper presents the formulation and practical implementation of positioning methodologies that compensate for the nonholonomic constraints of a mobile microrobot that is driven by two vibrating direct current (DC) micromotors. The open-loop and closed-loop approaches described here add the capability for net sidewise displacements of the microrobotic platform. A displacement is achieved by the execution of a number of repeating steps that depend on the desired displacement, the speed of the micromotors, and the elapsed time. Simulation and experimental results verified the performance of the proposed methodologies.